The causal effect of private and organizational climate-related identity on climate protection activities: Evidence from a framed field experiment in Japan - Toshihide Arimura; Elke D. Groh; Miwa Nakai; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2022)
Based on data for more than 2,400 citizens in Japan, this paper empirically examines the effect of climate-related identity in private and organizational contexts on revealed climate protec-tion activities, measured through incentivized donations. To identify causal effects, we include the concept of priming in our framed field experiment. In line with previous studies, our econ-ometric analysis reveals that environmental attitudes are strongly positively correlated with climate protection activities. However, we cannot confirm causal effects of climate-related attitudes since the private climate-related treatment has no significant effect. In contrast, the organizational climate-related treatment has a significantly positive effect on donations of employed persons for climate protection. This result is especially driven by a significant effect at the intensive margin. It suggests possible spillovers from organizational environmental and climate protection activities on individual climate protection activities so that climate protec-tion in companies, institutions, or other organizations has the potential to increase private cli-mate protection. Our results thus suggest that the stimulation of organizational climate pro-tection activities by climate policy measures such as taxes or subsidies can lead to a double dividend, i.e. to direct climate protection and to climate protection activities of persons who are employed in these organizations. Our empirical analysis also reveals that the estimated effect of the organizational climate-related treatment is particularly strong in the small sub-group of executive officers, managers of firms, and self-employed persons. This result sug-gests that higher individual responsibility and decision-making authority as well as compe-tences, also in terms of climate-related decisions, lead to stronger causal effects of organiza-tional on private climate protection activities.
Keywords: Q54; Q58; D91; C93; 330; Climate protection activities; climate-related identity; private and organizational contexts; priming; non-state actors; framed field experiment